Intestinal bacterial population of healthy rats during the administration of chitosan and chitooligosaccharides - Koppová, Ingrid; Bures, Martin; Simnek, Jirí (Folia microbiologica, 2012)
The effect of the administration of chitosan (CS) and chitooligosaccharides (COS) on rat fecal microbiota was analyzed in this study. The profile of total bacterial population was monitored during 3 weeks of CS or COS application using denaturing gradient gel electrophoresis (DGGE) analysis of 16S rRNA gene amplicons. Quantitative PCR was used for monitoring possible changes in the levels of total bacteria and the levels of individual bacterial groups: Bifidobacteria, Clostridium leptum, Enterobacteriaceae, Lactobacillus–Streptococcus–Enterobacter, and Bacteroides–Prevotella. The DGGE profiles revealed a high complexity and individuality of each tested subject, and variations in the composition of band pattern were observed. CS or COS per os administration changed the profile and structure of the microbial ecosystem of the gastrointestinal tract of healthy rats. COS have, in most cases, an opposite effect compared with CS; only the Bacteroides–Prevotella bacterial group and Enterobacteriaceae were influenced in the same way. The Bifidobacteria group was not influenced by the administration CS and COS.